PREDIKSI FINANCIAL DISTRESS DENGAN MENGGUNAKAN METODE ALTMAN Z”-SCORE, SPRINGATE, DAN ZMIJEWSKI PADA PT MATAHARI DEPARTMENT STORE TBK PERIODE 2018-2020 - Zeze Zakaria Hamzah; Retnadinda Ari Putri; Erna Herlina (Institut Teknologi dan Bisnis Dewantara, 2022)
Financial Distress is a condition where the company’s finances are experiencing financial difficulties and are unable to meet various obligants (Hutabarat, 2021:27). This study aims to determine the level of corporate bankruptcy using the Altman Z”-score, Springate, and Zmijewski method analysisat PT Matahari Department Store Periode 2018-2020. From the result of these studies and measurements, it can be concluded that both of them predict PT Matahari Department Store as a compamy that is categorized as healthy in 2018 and 2019, and categorized as high risk of bankruptcy in 2020. Cause PT Matahari Department Store is categorized as a company those who are at high risk of going bankrupt are because of the pandemic Covid-19and the enactment of the PSBB policy so that it has an impact on a very dractic decline in the level of sales in 2020 as well as permanentand temporary store closures.